Astronomy and Planetary Science From Cryovolcanism to Black Holes and Galactic Evolution - Chemin, Yann-Henri (IntechOpen, 2022)
The decades ahead of us promise the enhancement of our understanding of the Sun, the planets, the stars, black holes, and all other astronomical objects in our universe. This book discusses such topics as extra-galactic radio sources, unified models of black hole accretion, wave propagation theory, cryovolcanism in the solar system, and the early oceans of Earth.